Evaluation of Quadrature Signal Generation Methods with Reduced Computational Resources for Grid Synchronization of Single-Phase Power Converters through Phase-Locked Loops - Lamo-Anuarbe, Paula; Pigazo-López, Alberto; Azcondo, Francisco J. (Electronics, 2021)
Low-cost single-phase grid connected converters require synchronization with the grid voltage to obtain a better response and protection under diverse conditions, such as frequency perturbations and distortion. Phase-locked loops (PLLs) have been used in this scenario. This paper describes a set of quadrature signal generators for single-phase PLLs; compares the performances by means of simulation tests considering diverse operation conditions of the electrical grid; proposes strategies to reduce the computational burden, considering fixed-point digital implementations; and provides both descriptive and quantitative comparisons of the required mathematical operations and memory units for implementation of the analyzed single-phase PLLs.
Keywords: synchronization; phase-locked loop; PLL; computational burden; digital implementation; single-phase; low-cost; low-voltage; JCR; Scopus